Cibercidadania: a virtualização na Comunicação Pública contemporânea - Brito, José Augusto Pereira (Organicom, 2006)
Transformations on the current Public Communication are analyzed in view of the government social function for the informational inclusion, the citizenship in democracy by the technology, and the e-government, having the digital information, the on-line services, ethics in the virtual environment, and the network interactive communication as the society and organizations support.